A comparative analysis of translation strategies on slang words in the movie Deadpool 2 between internet fansub and professional translators - Muhammad Aprianto Budie Nugroho; Sanita Triksi Shepia (University of Muhammadiyah Purwokerto, 2019)
This research focuses on the translation of slang words and the strategies used by the translators of Internet version (IT) and DVD version (DT) in Deadpool 2 movie. The purpose of this research is comparing the translation of slang words and the useof translationstrategies by the two translators. The research employs a qualitative method with a case study as the design of the research. In collecting data NTC’s Dictionary of American Slang by Spears is used in clasifying slang words in the dialogue of Deadpool 2 movie. In analyzing and comparing the strategies, Baker’s (1992) theory is applied. The result of this research shows that; there are 65 slang words found in the movie. IT translated 47 slang words, and DT rendered 39 slang words. The interesting finding is that 38slang words are translated differently. Other 27 is the same. Seen from its translation strategy, five strategies are used by IT. Those are translation by a more general word, translation by omission, paraphrase using related word, paraphrase using unrelated word, andtranslation using a loan word. Meanwhile, DT employed six strategies, i.e.translation by a more general word, translation by omission, paraphrase using related word, paraphrase using unrelated word, translation using a loan word, and translation by less expressive word.